2019
DOI: 10.1155/2019/6831520
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Roles of Berberine in Gastrointestinal Cancers

Abstract: Berberine (BBR) is an isoquinoline alkaloid isolated from various types of plants, including those from the Berberidaceae, Ranunculaceae, and Papaveraceae families. It has long been used in traditional Chinese medicine for treating diarrhea and gastrointestinal disorders. The medicinal properties of BBR include antimicrobial, anti-inflammatory, antioxidative, lipid-regulatory, and antidiabetic actions. Importantly, the efficacy of BBR against cancers has been assessed in several experimental studies and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Moreover, CASC2 lncRNA binds to the Au-rich element-binding factor 1 (AUF1), which blocks the binding of AUF1 to Bcl-2 mRNA, thereby inactivating Bcl-2 translation [ 56 ]. There are many antitumor mechanisms induced by BBR in human colorectal cancer cells, such as suppression of cell viability, induction of cell apoptosis, and upregulation of CASC2 lncRNA [ 56 , 57 ]. Berberine also modulates the expression of the micro-RNA-429 (MIR-429) in colorectal cancer [ 58 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Moreover, CASC2 lncRNA binds to the Au-rich element-binding factor 1 (AUF1), which blocks the binding of AUF1 to Bcl-2 mRNA, thereby inactivating Bcl-2 translation [ 56 ]. There are many antitumor mechanisms induced by BBR in human colorectal cancer cells, such as suppression of cell viability, induction of cell apoptosis, and upregulation of CASC2 lncRNA [ 56 , 57 ]. Berberine also modulates the expression of the micro-RNA-429 (MIR-429) in colorectal cancer [ 58 ].…”
Section: Anticancer Perspectivesmentioning
confidence: 99%
“…Accordingly, the evidence from in vivo studies has confirmed that BBR exerts enormous therapeutic potential on various diseases, including cardiovascular diseases [27], metabolic diseases [28], inflammatory diseases [29] and cancers [30]. In terms of modern biomedical studies, the anti-cancer activities of BBR have been demonstrated, which were correlated to inhibit the proliferation, growth, and metastasis of tumors, including gastric cancer, pancreatic cancer, breast cancer, lung cancer, liver cancer and colorectal cancer [31]. Liu and colleagues found that BBR can inhibit the growth, migration/invasion of CRC cells via the COX-2/PGE2 mediated JAK2/STAT3 signaling pathway [32].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effect of berberine on depression has also been confirmed by numerous experiments. Studies have found that berberine can exert antidepressant effect by inhibiting neuroinflammation and regulating brain biogenic amines (Yin et al 2008 ; Hu et al 2019 ). What’s more, berberine can greatly shorten the immobility time of mice in FST and TST in animal experiments (Peng et al 2007 ; Lee et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%